Sequence variant affects GCSAML splicing, mast cell specific proteins, and risk of urticaria - Ragnar P. Kristjansson; Gudjon R. Oskarsson; Astros Skuladottir; Asmundur Oddsson; Solvi Rognvaldsson; Gardar Sveinbjornsson; Sigrun H. Lund; Brynjar O. Jensson; Edda L. Styrmisdottir; Gisli H. Halldorsson; Egil Ferkingstad; Grimur Hjorleifsson Eldjarn; et al. (Communications Biology, 2023)
Abstract Urticaria is a skin disorder characterized by outbreaks of raised pruritic wheals. In order to identify sequence variants associated with urticaria, we performed a meta-analysis of genome-wide association studies for urticaria with a total of 40,694 cases and 1,230,001 controls from Iceland, the UK, Finland, and Japan. We also performed transcriptome- and proteome-wide analyses in Iceland and the UK. We found nine sequence variants at nine loci associating with urticaria. The variants are at genes participating in type 2 immune responses and/or mast cell biology (CBLB, FCER1A, GCSAML, STAT6, TPSD1, ZFPM1), the innate immunity (C4), and NF-κB signaling. The most significant association was observed for the splice-donor variant rs56043070[A] (hg38: chr1:247556467) in GCSAML (MAF = 6.6%, OR = 1.24 (95%CI: 1.20–1.28), P-value = 3.6 × 10-44). We assessed the effects of the variants on transcripts, and levels of proteins relevant to urticaria pathophysiology. Our results emphasize the role of type 2 immune response and mast cell activation in the pathogenesis of urticaria. Our findings may point to an IgE-independent urticaria pathway that could help address unmet clinical need.